Operationalising cognitive fatigability in multiple sclerosis: a Gordian knot that can be cut? - Harrison, A. M.; das Nair, Roshan; Moss-Morris, Rona (Sage, 2016)
Background: Researchers have attempted to operationalise objective measures of cognitive fatigability in multiple sclerosis (MS) to overcome the perceived subjectivity of patient-reported outcomes of fatigue (PROs). Measures of cognitive fatigability examine decrements in performance during sustained neurocognitive tasks.